2020
DOI: 10.1371/journal.pone.0229717
|View full text |Cite
|
Sign up to set email alerts
|

On the genus Sabidius Strelzov, 1973 (Annelida: Paraonidae), with a redescription of the type species and the description of a new species

Abstract: Two species of Sabidius Strelzov, 1973 were collected during a benthic survey, from 10-3,000 m deep, in Espírito Santo Basin, off southeastern Brazilian coast. Those species are S. cornatus (Hartman, 1965) and S. antennatus sp. nov. The genus Sabidius was monotypic until the present study, in which a new species is proposed, together with a redescription of the type species, with expansion of the geographic distribution of the genus and of the type species. The diagnostic feature of the genus is the morphology… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The prostomium is usually triangular, sub-trapezoidal, or rounded, but in some species of the genera Aricidea (e.g., Aricidea trilobata Imajima, 1973 [188]) and Sabidius (e.g., Sabidius cornatus (Hartman, 1965) [58]), it is more or less strongly trilobed. Sabidius species are peculiar in having a thickened cuticle on the anterior margin of the prostomium [189]. The presence or absence of a single antenna has been originally used to separate different genera [35], but it has been shown that all monophyletic lineages within Paraonidae include both species with and without antenna [14].…”
Section: Morphologymentioning
confidence: 99%
“…The prostomium is usually triangular, sub-trapezoidal, or rounded, but in some species of the genera Aricidea (e.g., Aricidea trilobata Imajima, 1973 [188]) and Sabidius (e.g., Sabidius cornatus (Hartman, 1965) [58]), it is more or less strongly trilobed. Sabidius species are peculiar in having a thickened cuticle on the anterior margin of the prostomium [189]. The presence or absence of a single antenna has been originally used to separate different genera [35], but it has been shown that all monophyletic lineages within Paraonidae include both species with and without antenna [14].…”
Section: Morphologymentioning
confidence: 99%
“…Regarding the Brazilian coast, previous studies on paraonids registered the presence of six genera and 38 species, most of them from shallow waters [28]. Few systematic studies have been conducted on Brazilian paraonids [11,[29][30][31], so most (62%) of the previous records for the family in Brazil come from gray literature and papers with an ecological approach, in which specimens descriptions and illustrations are not given [28]. For this reason, most of these records are questionable.…”
Section: Introductionmentioning
confidence: 99%